Association of diastolic blood pressure with cardiovascular events in older people varies upon cardiovascular history. Issue 4 (April 2018) - Wijsman, Liselotte W.; Muller, Majon; de Craen, Anton J.M.; Jukema, J. Wouter; Westendorp, Rudi G.J.; Mooijaart, Simon P.
Abstract : Background: In older age, a low DBP has been associated with increased risk of cardiovascular events, especially in frail older people. We tested the hypothesis that low DBP is associated with a high risk of cardiovascular events in people with a previous history of cardiovascular disease, as a proxy of vascular impairment. Methods: We included 5804 participants (mean age 75 years) from the PROspective Study of Pravastatin in the Elderly at Risk (PROSPER) who as part of the trial were intensively monitored for an average period of 3.2 years. DBP was categorized in low (<70 mmHg), normal (70–90 mmHg) or high (>90 mmHg). Cox proportional hazards analyses were used to estimate hazard ratio with 95% confidence intervals (CI); analyses were stratified for cardiovascular history. Results: Participants with low DBP had a 1.24-fold (1.04; 1.49) increased risk of cardiovascular events compared with those with normal DBP. After further adjusting for cardiovascular factors, this association attenuated to 1.05 (0.86; 1.28). A previous history of cardiovascular disease significantly modified the relation between DBP and risk of cardiovascular events ( P -interaction 0.042). In participants without a history of cardiovascular disease, DBP was marginally significantly associated with an increased event risk (hazard ratio (95% CI) per 10 mmHg increase in DBP 1.08 (0.99; 1.18), P value = 0.07), whereas in participants with a history of cardiovascular disease, higher DBP was associated with a decreased risk of cardiovascular events (hazard ratio (95% CI) per 10 mmHg increase in DBP 0.92 (0.85; 0.99, P value = 0.018). These risk estimates were independent of potential confounders, including classical cardiovascular risk factors. Conclusion: The association of DBP with cardiovascular events in older people varies upon their previous history, showing that in participants with preexisting cardiovascular diseases, a higher DBP associates with a decreased risk of future cardiovascular events. Abstract : Supplemental Digital Content is available in the text